Applications of Hydrogenous Species for Initiation of Carbon Monoxide/Air Premixed Flame - Annas Fauzy; Guan-Bang Chen; Ta-Hui Lin (Energies)
Carbon monoxide (CO) is classified as a simple fuel that contains one carbon and one oxygen atom. The oxidation of CO with an oxidizer is relatively unusual, with the oxidation of CO having a slow reaction time. The addition of a small amount of “hydrogenous” species, such as H2, H2O, and CH4, will substantially increase the reaction time. This study numerically investigated and compared the effects of different hydrogenous species addition on the premixed CO/air flames, which act as the initiation of a CO/air flame, on the adiabatic flame temperature, laminar flame speed, and heat release rates at standard conditions (298 K and 1 atm pressure) using San Diego Mechanism. The results showed that the addition of critical hydrogenous species distinguished the difference between dry and wet CO/air oxidation, in which different hydrogenous species have an identical critical value. Adding different hydrogenous species and different addition ratios has an indistinguishable adiabatic flame temperature, while adding CH4 has a higher laminar flame speed distribution compared with H2 and H2O addition, respectively. Furthermore, the laminar flame speed positively correlates with the net heat release rate, which adding CH4 has a noticeable increase on the net heat release rate. Adding more hydrogenous species makes the reactant more reactive and moves the reaction zone upstream. Finally, the dominant reactions to the heat release rate are identical in different hydrogenous species addition, where R23: CO + O (+M) ⇌ CO2 (+M) becomes the most contributed reaction.